A note on dilations and martingales - Martin L. Jones (International Journal of Mathematics and Mathematical Sciences)
The purpose of this note is to investigate the effect of dilations on martingales and to give conditions under which a dilated martingale will retain the martingale property. The technique of dilating the joint distribution of a sequence of random variables has applications in optimal stopping theory and the study of prophet inequalities where martingales play a significant role.